Case report: From sequence to solution: tailoring treatment for transformed follicular lymphoma (DLBCL) through next generation sequencing study - Bouroumeau, Antonin; Perdikis-Prati, Sarah; Lang, Noémie (Frontiers in Oncology, 2024)
Immune checkpoint blockade (ICB) has indeed transformed the outlook for many advanced-stage solid tumors, yet its effectiveness in hematological malignancies has been particularly limited, with success predominantly demonstrated in classical Hodgkin lymphoma (cHL) and immune-privilege subtypes of non-Hodgkin lymphoma (NHL).In this report, we present an impactful case of a 71-year-old man grappling with refractory follicular lymphoma (rFL) that had progressed to a high-grade lymphoma, leaving no conventional treatment options on the table. Notably, the histological examination of the tumor tissue revealed a markedly elevated PD-L1 expression, illuminating the potential for immunotherapy to be effective. Additionally, comprehensive gene sequencing unveiled a moderate tumor mutational burden (TMB), deepening our understanding of the tumor's molecular intricacies. As his health declined with no access to cell therapies or clinical trials at that time, a combination treatment of PD-1 ICB and an anti-CD20 drug surprisingly led to a significant improvement in his condition and long-term remission.While PD-1 ICB therapy has historically shown limited responses in non-Hodgkin lymphomas (NHL), this case serves as a beacon of optimism, underscoring the promise of combining immunotherapy modalities and the potential of comprehensive molecular assessments in charting innovative treatments for extensively treated NHL patients. The quest for predictive biomarkers to gauge treatment response remains a formidable challenge. This report serves as a testament to the ever-evolving landscape of cancer treatment, where precision medicine and immunotherapy continue to unlock new possibilities for those confronting the most challenging malignancies.